(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The State programs implemented in New Uzbekistan require the socio-economic and cultural protection of young people, the improvement of their lifestyle, the further improvement of their cultural and ideological outlook, and most importantly, the upbringing of each young person in the spirit of humanity, patriotism, hard work, courage, courage, national customs, values, and traditions in order to positively determine their current and future lives. Therefore, the need for the topic to eliminate existing problems through historical study and scientific analysis, further instilling the spirit of patriotism in young people, and acquiring modern science and professions in line with world standards is determined by the topic.